1995
DOI: 10.1016/1074-7613(95)90010-1
|View full text |Cite
|
Sign up to set email alerts
|

Specific T cell recognition of minimally homologous peptides: Evidence for multiple endogenous Ligands

Abstract: The T cell receptor (TCR) can interact with a spectrum of peptides as part of its ligand, including the immunogenic peptide, variants of this peptide,and apparently unrelated peptides. The basis of this broad specificity for ligand was investigated by substitution analysis of a peptide antigen and functional testing using a B cell apoptosis assay. A peptide containing as few as 1 aa in common with this peptide could stimulate a specific T cell response. Two endogenous ligands, an agonist and a partial agonist,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
118
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(121 citation statements)
references
References 63 publications
3
118
0
Order By: Relevance
“…T-cell cross-reactivity based on minimal epitope identity has been shown for both CD4 ϩ and CD8 ϩ T cells in different experimental setups. [23][24][25] These reports clearly demonstrate that peptide identity based on only 1 or 2 amino acid residues is sufficient to explain T-cell activation by nonhomologous peptides. However, the recognition of peptide analogues by mature T cells seldom leads to full activation of the T cell and in some cases peptide analogues even act as TCR antagonists or partial agonists involved in downregulation of T-cell responses.…”
Section: Ctl Killing Of Natural Targetsmentioning
confidence: 99%
“…T-cell cross-reactivity based on minimal epitope identity has been shown for both CD4 ϩ and CD8 ϩ T cells in different experimental setups. [23][24][25] These reports clearly demonstrate that peptide identity based on only 1 or 2 amino acid residues is sufficient to explain T-cell activation by nonhomologous peptides. However, the recognition of peptide analogues by mature T cells seldom leads to full activation of the T cell and in some cases peptide analogues even act as TCR antagonists or partial agonists involved in downregulation of T-cell responses.…”
Section: Ctl Killing Of Natural Targetsmentioning
confidence: 99%
“…[14][15][16][17][19][20][21][22][23][24][25] In the present study, to further analyze the TCR ligands of the PDC-E2 163-176 -reactive T cells, we investigated the response of PDC-E2 163-176 -reactive cloned T-cell lines to a panel of single amino acid-substituted peptides derived from the PDC-E2 163-176 peptide. We found that each T-cell clone had a different pattern of reactivity to a panel of these analogue peptides, indicating the presence of a variety of T-cell repertoire for a single TCR ligand such as the PDC-E2 163-176 peptide/HLA DR53 complex.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular mimicry between foreign and self-antigens have been implicated as a possible mechanism for the activation of these self-reactive T cells. [14][15][16][17][18][19] Previously, we illustrated the evidence of molecular mimicry at the T-cell clonal level in PBC; one molecular mimicry peptide derived from Escherichia coli PDC-E2 activated a human PDC-E2 163-176 -reactive cloned T-cell line generated from a patient with PBC. 11 In addition, we illustrated the evidence of cross-recognition of human OGDC-E2 100-113 peptide (DEVVCEIETDKTSV), which is a distinct but related mitochondrial antigen recognized by some AMAs, by human PDC-E2 163-176 -reactive cloned T-cell lines established from PBC patients.…”
mentioning
confidence: 99%
“…The pathogenic importance of the latter recognition has led us to investigate the structural basis of this cross-reactivity. While many structural studies of multiple peptide recognition on a single self-MHC molecule exist (10,11), precedents for dual MHC recognition by one TCR involve alloreactivity (12) or xenoreactivity (13).…”
mentioning
confidence: 99%